CURRENT STATUS OF ACCESS TO HEALTHCARE SERVICES AMONG PATIENTS WITH RIFAMPICIN-RESISTANT TUBERCULOSIS IN THAI NGUYEN PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of access to healthcare services and to identify factors influencing healthcare access among patients with Rifampicin-resistant tuberculosis in Thai Nguyen province.Methods: A cross-sectional descriptive study was conducted among 70 inpatients diagnosed with Rifampicin-resistant tuberculosis at Thai Nguyen Lung Hospital.Results: Overall, 60% of patients had good access to healthcare services. The median diagnostic delay was 28.5 days; 22.9% of patients experienced treatment interruption for more than two weeks; and 34.3% incurred additional out-of-pocket expenditures beyond health insurance coverage. Factors associated with good access to healthcare services included adequate knowledge of the disease, educational attainment at high school level or above, distance to the DOT facility ≤ 10 km, good treatment adherence, absence of comorbidities, and no additional out-of-pocket costs.Conclusion: Access to healthcare services among patients with Rifampicin-resistant tuberculosis in Thai Nguyen remains moderate and is influenced by multiple social, economic, and health system- related factors.
Keywords: Rifampicin-resistant tuberculosis, access, healthcare services, Thai Nguyen.